Pengaruh Akuntansi Konservatif, Ukuran Perusahaan, Default Risk, Dan Pertumbuhan Perusahaan Terhadap Koefisien Respon Laba (ERC) - Desrianti Dewi (Fakultas Ekonomi dan Bisnis Universitas Pasundan, 2020)
This study aims to provide an overview and influence of conservative accounting, company size, default risk, company growth and earnings response coefficient (ERC) either partially or simultaneously in mining sector companies listed on the Indonesia Stock Exchange 2014-2018. The research method used is descriptive verification method. The population of this study were 38 companies. Purposive sampling of 10 companies that meet the criteria. The data analysis method was carried out by multiple linear regression analysis, classical assumption test, correlation analysis, and determination coefficient. While the hypothesis testing used is the partial test statistical method (t test) and simultaneous test (F test) using SPSS 24. The results of this study indicate that partially conservative accounting and firm size have no effect on the earnings response coefficient (ERC), while the default risk and company growth affect the earnings response coefficient (ERC). Simultaneously conservative accounting, firm size, default risk, and company growth affect the earnings response coefficient (ERC).